2017
DOI: 10.1016/j.jaad.2016.10.027
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory bowel disease among patients with psoriasis treated with ixekizumab: A presentation of adjudicated data from an integrated database of 7 randomized controlled and uncontrolled trials

Abstract: From an integrated database of 7 ixekizumab psoriasis trials, CD and UC cases were uncommon (<1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 25 publications
3
46
0
1
Order By: Relevance
“…Overall, a total of 12 cases of IBD were reported among 12 614 patients in the treatment arms corresponding to an incidence of 2.4 cases per 1000 patient‐year, whereas zero cases of new onset IBD were reported among 4076 patients in the placebo group. The low incident rate reported in the current meta‐analysis is similar to a rate of 1.9/1000 patient‐year, which was reported by a group that investigated the risk of IBD associated with ixekizumab in both RCTs and uncontrolled trials . Similar incident rate has also been observed in a long‐term safety study of secukinumab in patients with plaque psoriasis .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, a total of 12 cases of IBD were reported among 12 614 patients in the treatment arms corresponding to an incidence of 2.4 cases per 1000 patient‐year, whereas zero cases of new onset IBD were reported among 4076 patients in the placebo group. The low incident rate reported in the current meta‐analysis is similar to a rate of 1.9/1000 patient‐year, which was reported by a group that investigated the risk of IBD associated with ixekizumab in both RCTs and uncontrolled trials . Similar incident rate has also been observed in a long‐term safety study of secukinumab in patients with plaque psoriasis .…”
Section: Discussionsupporting
confidence: 88%
“…which was reported by a group that investigated the risk of IBD associated with ixekizumab in both RCTs and uncontrolled trials. 47 Similar incident rate has also been observed in a long-term safety study of secukinumab in patients with plaque psoriasis. 48 The incidence rate of 2.4 per 1000 patient-years found in our study falls within the reported range of 0.29 to 4.6 per 1000 person-years among observational studies assessing the risk of IBD among psoriasis patients, but appears to be much higher compared to the incidence of 0.18 per 1000 person-years of the US general population.…”
Section: Meta-analysis Of the Risk Of Diarrhoea With Anti-il17 Agentssupporting
confidence: 65%
See 1 more Smart Citation
“…Studies have shown that the prevalence of Crohn's disease and ulcerative colitis has increased in patients with psoriasis. [21][22][23][24] However, Reich et al 25 reported that Crohn's disease and ulcerative colitis cases were uncommon (<1%) in ixekizumab-treated patients, based on the integrated database of seven ixekizumab psoriasis trials. These results are consistent with those observed in the present analysis of integrated database of 11 ixekizumab psoriasis trials.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a review of an integrated database of seven ixekizumab (another anti-IL-17A monoclonal antibody) psoriasis trials, including 4209 patients (6480 patient-exposure years), suggested incident cases of CD or UC were uncommon (<1%). 174 …”
Section: Pathways That Exacerbate Ibdmentioning
confidence: 99%